Overcoming the Innovator's Paradox - Dyer, Jeff; Furr, Nathan; Hendron, Mike (MIT Sloan Management Review, 2020)
People tend to think the biggest innovation challenge is finding great ideas. But many great ideas die when entrepreneurs fail to persuade others of their potential. Indeed, the more novel the idea, the harder it is to get resources for it.
Online resource; Title from title page (viewed July 20, 2020)